2017
DOI: 10.1161/circinterventions.116.004244
|View full text |Cite
|
Sign up to set email alerts
|

Independent Modular Filter for Embolic Protection in Carotid Stenting

Abstract: Background-Embolic protection during carotid artery stenting reduces the rate of thromboembolic events. The Wirion Embolic Protection System is used to deploy an independent distal filter using any 0.014″ guidewire. WISE study (Wirion Study Europe) evaluated the safety and performance of Wirion Embolic Protection System in patients undergoing carotid artery stenting. Methods and Results-A prospective, multicenter, nonrandomized, open-label, single-arm study of carotid artery stenting in high surgical risk pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Based on the available data, the Wirion distal filter was associated with high technical and clinical success in both the carotid and femoropopliteal vascular beds. These data eventually led to US FDA approval for application of the Wirion EPS at the carotid and the femoropopliteal segments [37,39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the available data, the Wirion distal filter was associated with high technical and clinical success in both the carotid and femoropopliteal vascular beds. These data eventually led to US FDA approval for application of the Wirion EPS at the carotid and the femoropopliteal segments [37,39].…”
Section: Discussionmentioning
confidence: 99%
“…One study was identified across literature reporting on performance of the Wirion EPS in patients undergoing CAS (NCT01783639) [37]. This was a prospective, multicenter, single-arm study enrolling 120 high surgical risk patients that underwent CAS for ≥50 and ≥80% stenosis in symptomatic and asymptomatic carotid disease, respectively [37]. The study demonstrated 98.3% procedural success and 100% periprocedural survival rate, with stroke occurring in only 2.5% of the cases [37].…”
Section: Wirion Filter Utilization During Casmentioning
confidence: 99%
See 2 more Smart Citations
“…Scheinert et al 10) reported that the use of distal EPD is safe and effective in patients undergoing high-risk surgeries. Sridhara et al 11) stated that with proper technique, CAS can not only reduce stroke but also prevent stroke-associated cognitive decline, vascular injury, etc.…”
Section: Discussionmentioning
confidence: 99%